The individual experience of ageing patients and the current service provision in the context of Italian forensic psychiatry: a case-study - Di Lorito, Claudio; Castelletti, Luca; Tripi, Giuseppa; Gandellini, Maria Gloria; Dening, Tom; Völlm, Birgit (Lippincott Williams & Wilkins, 2017)
Introduction. Following the recent development of residential units for the execution of security measures (REMS) managed by the National Health Service and the closing down of forensic psychiatric hospitals, no study has been conducted to investigate the individual experience of ageing patients and to assess whether the new service is adequately meeting their needs. We aim to explore the experience of the service of a sample of patients aged 50 years old and above living in one of the Italian REMS.